Critical Land, Environmental Damage, and Revitalization Efforts through the Development of Coffee Agriculture - Triya Ayu Retnaningtyas (Indonesian Journal of Social Responsibility Review (IJSRR), 2022)
The Dieng Plateau which is on the slopes of Mount Sindoro and Sumbing, Wonosobo Regency is very crucial as a water catchment area in Central Java Province. The Dieng Plateau as a protected function forest area should be an area that is protected from production activities and human activities that have potential to damage its protected function. These protected areas are massively exploited for the sake of fulfilling human needs, resulting in environmental damage in various areas. One effort to restore this situation is by revitalizing land through the development of coffee farming. The purpose of this paper is to discuss efforts to revitalize land through the development of coffee farming in Dieng Plateau area. This study uses a descriptive qualitative method with a character study approach. The development of coffee plants can be an effort to conserve forests, maintain water absorption, and reduce natural disasters. Tambi Coffee Plantation is a coffee plantation area located in Tambi Village, Wonosobo Regency. Coffee root can prevent erosion. In addition to revitalization to reforest deforested land in the Dieng Plateau, farmers can benefit from the coffee seeds planted. The development of coffee farming is now making Dieng Plateau farmers more empowered and prosperous.